O ensino primário em Caxias do Sul (1890-1930) : vestígios da cultura material escolar - Vanz, Samanta (My University, 2020)
This paper aims at understanding to what extend the historical traces of objects, artifacts and materials in primary schools in Caxias do Sul, from between 1890 and 1930, contributed for the making of a historical narrative in the context of primary school. The time frame for this research starts in 1890, year of the foundation of the municipality of Caxias do Sul, going to 1930, when Duque de Caxias Complimentary School was founded. The latter changed the teacher education and training in the region, as well as the entire context of primary school. The theories and methods used for this research are based on the Cultural History field, in a dialog with historians such as Burke (1992; 2008), Chartier (1990; 1991; 2009), Le Goff (1990) and Pesavento (2014). As for the Education theoretical background, this work is based on the concept of School Cultures, by Viñao Frago (1995; 2001), Julia (2001) and Escolano (2017). The investigation used the method of historical document analysis, using as main documentary source the correspondence between teachers, school inspectors and municipal intendents, as well as school applications and inventories, municipal reports, acts and decrees, and printed matter. The narrative made through material traces from analysis of the documentary sources clarified how the schooling process developed inside individual schools. Material culture identified in the correspondences, applications and inventories made it possible to picture situations in which the daily practices corroborated the republican project of a positivistic country, focused on civilization and progress. It should be highlighted that objects used to read, write and count, as well as furniture and objects that instructed via “stuff lessons”, make evident which were the ways of doing, adapting and producing a school culture. This study found traces of a network of involved subjects in the schooling process besides students and teachers, such as school inspectors, intendents, newspapers, families and the whole community. The importance of such a School Culture is made evident, especially as constitutive of the school environment and mediator of the relations between subjects, allowing practices, conducts, creating routines, representations, reflecting on the way teachers and students used and appropriated the given context. The traces analyzed point toward the statement that school objects were important in the schooling process, however, unlike what was prescribed, the intuitive method was not common in class, which emphasized practical knowledges such as reading, writing and counting. Finally, it is acknowledgeable that even facing lack of available material resources, there was a movement by the involved subjects with primary education aiming at building a school material Culture that could contribute, given the scenario, to the education of the children of the colonizers who established their families in the community since the 19th century.
Esta pesquisa buscou compreender como os vestígios de objetos, artefatos e materiais presentes nas escolas primárias de Caxias do Sul entre os anos de 1890 e 1930 contribuíram para compor uma narrativa histórica sobre o ensino primário em Caxias do Sul. O recorte temporal adotado inicia-se em 1890, quando é fundado o município de Caxias do Sul, estendendo-se até 1930, quando a Escola Complementar Duque de Caxias é inaugurada, influenciando na formação dos professores da região e consequentemente no contexto da educação primária. Os pressupostos teórico-metodológicos são ancorados na História Cultural, a partir do diálogo com historiadores como Burke (1992; 2008), Chartier (1990; 1991; 2009), Le Goff (1990) e Pesavento (2014). Para possibilitar a tessitura teórica, também são utilizados os conceitos de Culturas Escolares a partir de Viñao Frago (1995; 2001), Julia (2001) e Escolano (2017). A investigação mobilizou a metodologia da análise documental histórica, considerando como principais fontes documentais as correspondências de professores, inspetores escolares e intendentes municipais, solicitações e inventários escolares, relatórios da intendência, atos e decretos e impressos. A narrativa realizada por meio dos vestígios materiais identificados nas análises das fontes documentais permitiu compreender como o processo de escolarização foi se desenvolvendo no interior das escolas isoladas. A materialidade identificada nas correspondências, solicitações e inventários permitiu recompor cenários em que as práticas se desenvolveram corroborando para o projeto republicano e positivista de pátria, civilização e progresso. Destaca-se que objetos escolares para ler, escrever e contar, assim como mobiliário e objetos que instruíam a partir das “lições de coisas”, evidenciam os modos de fazer, de adaptar e de produzir uma cultura escolar. O estudo produzido traz indícios de uma rede de sujeitos envolvidos no processo de escolarização além de alunos e professores, como inspetores escolares, intendentes, os impressos jornalísticos, as famílias dos alunos e a própria comunidade. Observa-se a importância dessa Cultura Escolar como constituinte do espaço escolar e mediadora das relações entre sujeitos, permitindo desenvolver condutas, práticas, instaurar rotinas, representações, refletindo nas formas de usos e apropriações por parte de professores e alunos. Os indícios pesquisados apontam para a afirmativa de que os objetos escolares eram importantes no processo de escolarização, mas que, diferentemente do prescrito, o método intuitivo foi pouco aplicado em aula, em que saberes práticos voltados para o ensino básico do ler, escrever e contar fizeram-se mais representativos. Por fim, reconhece-se que mesmo diante dos parcos recursos materiais existentes, houve movimento dos sujeitos envolvidos com a educação primária municipal para a constituição de uma Cultura material escolar que contribuísse, dentro do cenário possível, para a formação dos filhos dos colonos que se estabeleceram na comunidade a partir do século XIX.
Keywords: Ensino primário - Caxias do Sul (RS) - História; Educação - História; Cultura - Educação; Education, Primary - Caxias do Sul (Brazil) - History; Education - History; Culture - Education